The efficacy of a diabetes self-management education programme on the health literacy of T2DM patients from a first-level hospital in the Lusaka District of Zambia - Nambeye, Phililo (Stellenbosch : Stellenbosch University, 2023)
Thesis (MNutr)--Stellenbosch University, 2023.